Current European Union Economy Development Through the Supply Chain Strategy Challenges of Ukraine - Derevyanko, Maryna; Terekh, Olena; Lazarenko, Mykola; Bolotina, Anna; Zelensky, Vitaliy (ExcelingTech, 2020)
The study analyzes the national standardization and supply chain strategy system, namely, the changes that occur in connection with the economic part of the Ukraine-European Union Agreement, harmonization of the relevant regulatory framework of Ukraine with the European Union standards. It was revealed that the main obstacles to the free movement of goods and services are technical barriers rather than trade impediments. In order to coordinate EU technical regulations and the system of technical regulations in Ukraine (in the process of implementing the economic policy of European integration), the evolution of the formation of these systems was traced. The analysis of the international economic integration showed that it is most effectively and deeply implemented provided that a relatively small number of countries that have close and established trade and economic relations, as well as almost the same level of development, are united. In addition, the research described the integrity of the technical regulation system in the EU countries and its fundamental difference in terms of its perception and actual functioning in Ukraine. It has been noted that the reform of the legislation, principles, and infrastructure of the technical regulation system, standardization and supply chain strategy is aimed at improving the safety, quality and competitiveness of Ukrainian products; protecting the life and health of citizens; simplifying business climate; balancing current distortions and imbalances; introducing innovations through the application of international standards and the removal of technical barriers. However, the analysis of the basic laws of Ukraine on foreign economic activity revealed a number of problems associated with the formation of the economic policy of European integration, in particular the lack of a shared vision of the country's economic development and the formation of the concept, values, principles, and economic policy of European integration.